High inter‐ and intraspecific niche overlap among three sympatrically breeding, closely related seabird species: Generalist foraging as an adaptation to a highly variable environment?. Issue 1 (6th September 2019) - Dehnhard, Nina; Achurch, Helen; Clarke, Judy; Michel, Loïc N.; Southwell, Colin; Sumner, Michael D.; Eens, Marcel; Emmerson, Louise
Abstract: Ecological niche theory predicts sympatric species to show segregation in their spatio‐temporal habitat utilization or diet as a strategy to avoid competition. Similarly, within species individuals may specialize on specific dietary resources or foraging habitats. Such individual specialization seems to occur particularly in environments with predictable resource distribution and limited environmental variability. Still, little is known about how seasonal environmental variability affects segregation of resources within species and between closely related sympatric species. The aim of the study was to investigate the foraging behaviour of three closely related and sympatrically breeding fulmarine petrels (Antarctic petrels Thalassoica antarctica, cape petrels Daption capense and southern fulmars Fulmarus glacialoides ) in a seasonally highly variable environment (Prydz Bay, Antarctica) with the aim of assessing inter‐ and intraspecific overlap in utilized habitat, timing of foraging and diet and to identify foraging habitat preferences. We used GPS loggers with wet/dry sensors to assess spatial habitat utilization over the entire breeding season. Trophic overlap was investigated using stable isotope analysis based on blood, feathers and egg membranes. Foraging locations were identified using wet/dry data recorded by the GPS loggers and expectation‐maximization binary clustering. Foraging habitat preferences were modelled using generalized additive models and model cross‐validation. During incubation and chick‐rearing, the utilization distribution of all three species overlapped significantly and species also overlapped in the timing of foraging during the day—partly during incubation and completely during chick‐rearing. Isotopic centroids showed no significant segregation between at least two species for feathers and egg membranes, and among all species during incubation (reflected by blood). Within species, there was no individual specialization in foraging sites or environmental space. Furthermore, no single environmental covariate predicted foraging activity along trip trajectories. Instead, best‐explanatory environmental covariates varied within and between individuals even across short temporal scales, reflecting a highly generalist behaviour of birds. Our results may be explained by optimal foraging theory. In the highly productive but spatio‐temporally variable Antarctic environment, being a generalist may be key to finding mobile prey—even though this increases the potential for competition within and among sympatric species. Abstract : This article shows a striking case of closely related and sympatrically breeding species overlapping in their resource use across multiple dimensions. The very unusual results are best explained by high food availability in combination with spatio‐temporal environmental variability and mobile prey fields, requiring predators to respond opportunistically and show generalist foraging behaviour.